2017
DOI: 10.17306/j.afs.2017.0454
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value and chemical composition of Sudanese millet-based fermented foods as affected by fermentation and method of preparation

Abstract: Background. Although kissra and hulu-mur are well known millet-based foods in Sudan, the effect of fermentation and methods of preparation on their chemical compositions has not been thoroughly investigated. The aim of this study was to investigate the method of preparation and the composition of kisra, and hulu-mur. Material and methods. The effect of fermentation and method of preparation on the composition, and microbiological load were examined in millet flour during the preparation of Sudanese fermented f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…Adeoti et al (2017) also reported magnesium content for pearl millet that ranged from 340.27 mg/kg to 4769.9 mg/kg. Phosphorus was found in abundance in the types investigated, pearl millet types had the highest share, the result is in the same range of (295.55 mg/100 gm) reported by Mariod et al (2017), for pearl millet types. Phosphorus which is considered the precursor to energy in the body, Devi et al (2011) states that it has the benefit of boosting the energy content of the millet.…”
Section: Discussionsupporting
confidence: 81%
“…Adeoti et al (2017) also reported magnesium content for pearl millet that ranged from 340.27 mg/kg to 4769.9 mg/kg. Phosphorus was found in abundance in the types investigated, pearl millet types had the highest share, the result is in the same range of (295.55 mg/100 gm) reported by Mariod et al (2017), for pearl millet types. Phosphorus which is considered the precursor to energy in the body, Devi et al (2011) states that it has the benefit of boosting the energy content of the millet.…”
Section: Discussionsupporting
confidence: 81%
“…All analyses were performed in triplicate. Mariod, A. A., Idris, Y. M. A., Osman, N. M., Mohamed, M. A., Sukrab, A. M. A., Matthaus, B.…”
Section: Mineral Elements Extraction and Determinationmentioning
confidence: 99%
“…During the fermentation and production of millet hulu-mur there was a significant (P ≤ 0.05) increase in glucose and maltose due to the germination process of the millet seeds before fermentation. In MHAS the free sugars reach a maximum (9.04), the dominant sugar being Mariod, A. A., Idris, Y. M. A., Osman, N. M., Mohamed, M. A., Sukrab, A. M. A., Matthaus, B.…”
Section: Carbohydrate Content Of Millet and Millet-based Fermented Foodsmentioning
confidence: 99%
See 2 more Smart Citations